Antibiofilm effect of chlorhexidine-carrier nanosystem based on iron oxide magnetic nanoparticles and chitosan - Vieira, Ana Paula Miranda [UNESP]; Arias, Laís Salomão [UNESP]; de Souza Neto, Francisco Nunes [UNESP]; Kubo, Andressa Mayumi; Lima, Bruno Henrique Ramos; de Camargo, Emerson Rodrigues; Pessan, Juliano Pelim [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Monteiro, Douglas Roberto [UNESP] (Elsevier, 2019)
This study synthesized and characterized a chlorhexidine (CHX)-carrier nanosystem based on iron oxide magnetic nanoparticles (IONPs) and chitosan (CS), and evaluated its antimicrobial effect on mono- and dual-species biofilms of Candida albicans and Streptococcus mutans. CHX was directly solubilized in CS-coated IONPs and maintained under magnetic stirring for obtaining the IONPs-CS-CHX nanosystem. Antimicrobial susceptibility testing for planktonic cells was performed by determining the minimum inhibitory concentration (MIC) of the nanosystem and controls. The effects of the IONPs-CS-CHX nanosystem on the formation of mono- and dual-species biofilms, as well as on pre-formed biofilms were assessed by quantification of total biomass, metabolic activity and colony-forming units. Data were analyzed by the Kruskal-Wallis’ test or one-way analysis of variance, followed by the Student-Newman-Keuls’ or Holm-Sidak's tests (α = 0.05), respectively. Physico-chemical results confirmed the formation of a nanosystem with a size smaller than 40 nm. The IONPs-CS-CHX nanosystem and free CHX showed similar MIC values for both species analyzed. In general, biofilm quantification assays revealed that the CHX nanosystem at 78 μg/mL promoted similar or superior antibiofilm effects compared to its counterpart at 39 μg/mL and free CHX at 78 μg/mL. These findings highlight the potential of CS-coated IONPs as preventive or therapeutic agents carrying CHX to fight biofilm-associated oral diseases.
Keywords: Biofilms; Candida albicans; Chlorhexidine; Drug delivery systems; Magnetic nanoparticles; Streptococcus mutans